Quantitative response to nitrite from field-induced decomposition of the chloride adduct of RDX by reactive stage tandem ion mobility spectrometry. Issue 2 (10th November 2020) - Chiluwal, Umesh; Eiceman, Gary A.
Abstract : An additional dimension of selectivity for the determination of RDX by ion mobility spectrometry (IMS) was introduced through field-induced decomposition of RDX·Cl − to NO2 − on a spectral baseline free of interfering peaks. Abstract : An additional dimension of selectivity for the determination of RDX by ion mobility spectrometry (IMS) was introduced through field-induced decomposition of RDX·Cl − to NO2 − on a spectral baseline free of interfering peaks. In this variant of reactive stage tandem IMS, the explosive ion is decomposed selectively in the presence of an interferent and from significantly convolved peaks which were mobility isolated within a narrow range of drift times using dual ion shutters. Field-induced decomposition at 170 °C and field strength of 112 Td (∼16 kV cm −1 ) provided 15% decomposition yield and RDX, amid interferent, was detected decisively even when peaks differed in reduced mobility coefficients ( K o ) by only 0.02 cm 2 V −1 s −1 . A nitrite peak with S/N of 8.5 was observed with vapour concentrations of 54 ppb for RDX and 329 ppb for Interferent A in the ionization volume corresponding to 2 ng of RDX and 100 ng of Interferent A deposited on sample traps in the thermal desorption inlet. Findings on quantitative response suggest the presence of excessive amounts of interferent caused ionization suppression of RDX. Still, RDX was determined quantitatively using sequential processing of ions by mobility isolation, selective field induced decomposition, and mobility analysis in a second drift region.